Influence of academic stress and school bullying on self-harm behaviors among Chinese middle school students: The mediation effect of depression and anxiety - Chen, Hui; Guo, Huijuan; Chen, Haiyan; Cao, Xia; Liu, Jiali; Chen, Xianliang; Tian, Yusheng; Tang, Huajia; Wang, Xiaoping; Zhou, Jiansong (Frontiers in Public Health, 2023)
Objective: The purpose of this study was to explore the relationship between academic stress, school bullying and self-harm behaviors among Chinese middle school students and to further explore the impact of anxiety and depression on this relationship. Methods: The students (aged 12–16 years) in a middle school in Changsha city were invited to respond to a questionnaire through an online platform. The Patient Health Questionnaire-9 (PHQ-9) and Generalized Anxiety Disorder-7 (GAD-7) were used to assess the severity of anxiety and depressive symptoms, respectively. The experience of being bullied, academic stress, and self-harm behaviors were assessed using several questions on the basis of previous studies. Results: A total of 1,313 middle school students completed the study, and 3.40% and 4.10% of them reported suicide attempts (SAs) and nonsuicidal self-injury (NSSI), respectively. Univariate logistic regression analysis revealed that anxiety symptoms (OR=1.23, 95% CI: 1.18–1.28; OR=1.25, 95% CI: 1.19–1.31), depressive symptoms (OR=1.20, 95% CI: 1.16–1.25; OR=1.26, 95% CI: 1.20–1.31), school bullying (OR=3.8, 95% CI: 2.11–6.89; OR=2.76, 95% CI: 1.39–5.47), and academic stress (OR=2.20, 95% CI: 1.27–3.80; OR=3.80, 95% CI: 1.20–7.25) were common factors of NSSI and SAs. In addition, depressive symptoms showed a mediating effect on the association of school bullying and academic stress with SAs or NSSI, and anxiety symptoms showed a mediating effect on the association of school bullying and academic stress with NSSI only. Conclusion: Appropriate strategies are needed to reduce academic pressure and prevent school bullying. Meanwhile, negative emotions such as depression and anxiety should be evaluated and intervened in to prevent self-harm behaviors among middle school students.